Pathogenic Roles of CXCL10 in Experimental Autoimmune Prostatitis by Modulating Macrophage Chemotaxis and Cytokine Secretion - Hua, Xiaoliang; Ge, Shengdong; Zhang, Meng; Mo, Fan; Zhang, Ligang; Zhang, Jiong; Yang, Cheng; Tai, Sheng; Chen, Xianguo; Zhang, Li; Liang, Chaozhao (Frontiers in Immunology, 2021)
Chronic prostatitis and chronic pelvic pain syndrome (CP/CPPS) is an inflammatory immune disease that characterized by intraprostatic leukocyte infiltration and pelvic or perineal pain. Macrophages play vital roles in the pathogenesis of CP/CPPS. However, the mechanisms controlling the activation and chemotaxis of macrophages in CP/CPPS remain unclear. This study aimed to investigate the roles of CXCL10/CXCR3 pathway in the activation and chemotaxis of macrophages in CP/CPPS patients. The serums of CP/CPPS patients and healthy volunteers were collected and measured. Results showed that CXCL10 expression was significantly elevated, and was correlated with the severity of the CP/CPPS patients. Experimental autoimmune prostatitis (EAP) model was generated, and adeno-associated virus and CXCR3 inhibitors were used to treat EAP mice. Immunofluorescence, flow cytometry, and western blotting were used to analyze the functional phenotype and regulation mechanism of macrophages. Results showed that CXCL10 deficiency ameliorates EAP severity by inhibiting infiltration of macrophages to prostate. Moreover, CXCL10 could induce macrophage migrations and secretions of pro-inflammatory mediators via CXCR3, which consequently activated the downstream Erk1/2 and p38-MAPK signaling pathways. We also showed that prostatic stromal cell is a potential source of CXCL10. Our results indicated CXCL10 as an important mediator to be involved in the inflammatory infiltration and pain symptoms of prostatitis by promoting the migration of macrophages and secretion of inflammatory mediators via CXCR3-mediated ERK and p38 MAPK activation.